Local institutions, social capital and their role in forest plantation governance: lessons from two case studies of smallholder plantations in Paraguay. (1st April 2014) - Szulecka, J.; Secco, L.
Forestry activities are not implemented in a vacuum, but highly interlinked with other domains: social, cultural, institutional, economic, and political. Good governance that builds on effective local institutions and social capital enhancement becomes one of the key issues in studying and implementing forestry projects locally. The paper presents empirical evidence from a social forestry project implemented in the poorest departments of Eastern Paraguay. It provides a descriptive comparison of two neighbouring communities characterized by different institutions. There is a large difference in project performance in both areas in socio-economic terms. One community displayed high levels of social capital and was better prepared to take advantage of extension aid and "store" the acquired know-how. The other community, with low levels of social capital, benefited from the project activities only temporarily. The role of local institutions as project channels and the development of social capital are indicated as key factors for plantation projects to work effectively. Les activités de foresterie ne sont pas mises en pratique dans un vide social, mais fortement liées à d'autres secteurs et domaines: sociaux, culturels, institutionnels, économiques et politiques. La gestion prenant appui sur des institutions locales efficaces et une amélioration du capital social devient par conséquent une des questions-clés dans l'étude de la mise en pratique des projets de foresterie sur le terrain. Cet article présente des preuves empiriques recueillies dans le projet de foresterie sociale mis en place dans les départements les plus démunis de l'est du Paraguay. D'un point de vue socio-économique, les différences de performance des projets dans les deux zones sont conséquentes. Une communauté présentait de hauts niveaux de capital social et était mieux préparée à prendre avantage de l'offre d'aide et à emmagasiner le savoir-faire acquis. L'autre communauté, d'un faible capital social, ne bénéficiait des activités du projet que temporairement Le rôle des institutions locales comme conduits des projets, et le développement du capital social sont considérés comme l'un des facteurs clé pour une conduite efficace des projets de plantation.Las actividades forestales no se ejecutan en un vacío social, sino en estrecha relación con otros ámbitos: social, cultural, institucional, económico y político. Así pues, la buena gobernanza, basada en instituciones locales eficaces y la mejora del capital social, constituye una de las cuestiones clave en el estudio y la ejecución de proyectos forestales a escala local. Este articulo presenta pruebas empíricas de un proyecto de silvicultura social ejecutado en los departamentos más pobres de Paraguay oriental. Proporciona una comparación descriptiva de dos comunidades vecinas, caracterizadas por poseer instituciones diferentes. Se observó una gran diferencia en términos socio-económicos en el resultado de los proyectos en ambas áreas. Una comunidad mostró altos niveles de capital social y una mejor preparación para aprovechar el apoyo de los servicios de extensión y "almacenar" el conocimiento adquirido. La otra comunidad, con bajos niveles de capital social, se benefició de las actividades del proyecto tan solo de manera temporal. El papel de las instituciones locales como canales de ejecución y el desarrollo del capital social se señalan como factores clave para la efectividad de proyectos de plantaciones forestales.